2017
DOI: 10.1186/s12974-017-0839-0
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from Ganoderma lucidum attenuate microglia-mediated neuroinflammation and modulate microglial phagocytosis and behavioural response

Abstract: Background Ganoderma lucidum (GL) has been widely used in Asian countries for hundreds of years to promote health and longevity. The pharmacological functions of which had been classified, including the activation of innate immune responses, suppression of tumour and modulation of cell proliferations. Effective fractions of Ganoderma lucidum polysaccharides (GLP) had already been reported to regulate the immune system. Nevertheless, the role of GLP in the microglia-mediated neuroinflammation has not been suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 64 publications
1
66
0
Order By: Relevance
“…Preparation. The Aβ 42 O were prepared according to the previous publications with some modifications [23][24][25]. Aβ 42 peptides were purchased from (Genic-Bio, A-42-T-2).…”
Section: Aβ 42 Oligomersmentioning
confidence: 99%
“…Preparation. The Aβ 42 O were prepared according to the previous publications with some modifications [23][24][25]. Aβ 42 peptides were purchased from (Genic-Bio, A-42-T-2).…”
Section: Aβ 42 Oligomersmentioning
confidence: 99%
“…Aβ42 peptide was prepared as previously described (37). In brief, 1 mg Aβ42 was dissolved in 1 ml cold hexafluoroisopropanol (Sigma, 52517), and the solution was aliquoted into Protein LoBind tubes (Eppendorf, 030108094); each tube containing 50 µg Aβ42 was dried overnight at RT.…”
Section: Preparation Of Aβ42 Oligomersmentioning
confidence: 99%
“…49 The effectiveness of G. lucidum has been attributed to the polysaccharides fraction, which is 50 responsible for the stimulation of immune system [10,11]. The G. lucidum polysaccharides 51 (GLP) are believed to trigger an indirect antitumor mechanism in which the host immune 52 system is altered to target the tumor cells, meanwhile, it has been shown that GLP have the 53 ability to induce both innate and adaptive immune response [12][13][14][15][16]. The polysaccharides from 54 Chinese herbal medicine are regarded to involve in the activity regulation of immune cells and It is well known that cyclophosphamide (Cy) is a crucial chemotherapeutic drug in tumor 67 treatment, also induces numerous adverse effects, especially myelosuppression [25] and 68 immunosuppression [26,27].…”
Section: Introductionmentioning
confidence: 99%